2016
DOI: 10.1089/jmf.2015.3624
|View full text |Cite
|
Sign up to set email alerts
|

Aronia melanocarpaConcentrate Ameliorates Pro-Inflammatory Responses in HaCaT Keratinocytes and 12-O-Tetradecanoylphorbol-13-Acetate-Induced Ear Edema in Mice

Abstract: Abnormal expression of pro-inflammatory mediators such as cell adhesion molecules and cytokines has been implicated in various inflammatory skin diseases, including atopic dermatitis. In this study, we investigated the anti-inflammatory activity of Aronia melanocarpa concentrate (AC) and its action mechanisms using in vivo and in vitro skin inflammation models. Topical application of AC on mouse ears significantly suppressed 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced ear edema formation, as judged by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, excessive accumulation of ROS increases MMP activity, resulting in destruction of extracellular matrix (ECM) via collagen degradation [ 36 ]. Additionally, it has been reported that topical administration of AME ameliorates pro-inflammatory response via suppression of ROS-MAPK-NF-kB signaling pathway in a mouse model of tetradecanoylphorbol-13-acetate (TPA)-induced ear edema model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, excessive accumulation of ROS increases MMP activity, resulting in destruction of extracellular matrix (ECM) via collagen degradation [ 36 ]. Additionally, it has been reported that topical administration of AME ameliorates pro-inflammatory response via suppression of ROS-MAPK-NF-kB signaling pathway in a mouse model of tetradecanoylphorbol-13-acetate (TPA)-induced ear edema model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a limitation of the qualitative analysis of the ingredients contained in the OJE; it was poorly acknowledged which components of the OJE contributed to the protective effect against UVB-induced skin damage. In a few studies, AME showed an improvement in inflammation in a mouse model of ear edema [ 37 ], but the active ingredient of the extract was not reported. Our present results present not only the protective effect of the AME against UVB-induced skin damage but also present major ingredients of the AME containing phenolic compounds including chlorogenic acid and rutin.…”
Section: Discussionmentioning
confidence: 99%
“…Many pharmacologically active compounds isolated from natural products were developed as medicines (5). In particular, food-based compounds with anti-inflammatory activities have gained widespread attention owing to their safety (68). …”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is mediated by several factors and cellular signaling molecules that are released from macrophages (6,16). When the macrophages are stimulated by endotoxins, such as lipopolysaccharides (LPS), they release various proinflammatory mediators and cytokines, such as nitric oxide (NO), prostaglandin E 2 (PGE 2 ), tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported the use of DCFH-DA to inhibit ROS in cells. Goh et al (2016), described ROS inhibition in keratinocyte cell lines, HaCaT, and monocytic THP-1 cell lines treated with concentrate obtained from Alonia species [ 60 ]. Jensen et al (2015) reported ROS inhibition in polymorphonuclear cells in an extract obtained from blue-green algae [ 61 ].…”
Section: Resultsmentioning
confidence: 99%